2014
DOI: 10.4306/pi.2014.11.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder Like Behavioral Problems and Parenting Stress in Pediatric Allergic Rhinitis

Abstract: ObjectivePrevious studies have reported comorbidity of attention deficit and hyperactivity disorder (ADHD) and allergic diseases. The current study investigated ADHD like behavioral symptoms and parenting stress in pediatric allergic rhinitis.MethodsEighty-seven children (6-13 years old) with allergic rhinitis and 73 age- and sex-matched children of control group were recruited. Diagnosis and severity assessments of allergic rhinitis were determined by a pediatric allergist. The Parenting Stress Index-Short Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…Children who had ever been diagnosed with allergic rhinitis had higher risks of having inattentive and combined ADHD. A previous study had shown that only inattention symptoms (but not hyperactivity symptoms) were associated with allergic rhinitis (19), which is in agreement with the observations of our study. It has been demonstrated that asthmatic children exhibit more symptoms of hyperactivity/impulsivity in adolescence than controls (11).…”
Section: Discussionsupporting
confidence: 94%
“…Children who had ever been diagnosed with allergic rhinitis had higher risks of having inattentive and combined ADHD. A previous study had shown that only inattention symptoms (but not hyperactivity symptoms) were associated with allergic rhinitis (19), which is in agreement with the observations of our study. It has been demonstrated that asthmatic children exhibit more symptoms of hyperactivity/impulsivity in adolescence than controls (11).…”
Section: Discussionsupporting
confidence: 94%
“…These data showed that 78.5% of the children who were currently suffering from a chronic illness had allergy‐related diseases, such as allergic rhinitis, asthma, or atopic dermatitis (data not shown). Consistent with these findings, Lee et al () reported that children with allergic rhinitis manifested more somatization than do children without allergic rhinitis. Meanwhile, it was found that the obese children had higher scores on other problems (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…The boys exhibited a higher prevalence of externalizing behavioral problems than the girls and the older children manifested a higher prevalence of internalizing behavioral problems than their younger counterparts. Reportedly, chronic illness, such as allergic rhinitis, was significantly related to the manifestation of somatization and attentional problems (Lee et al , ), while overweight or obesity status was significantly associated with externalizing and internalizing behavioral problems among children (Datar & Sturm, ; Hwang et al , ). Furthermore, low levels of self‐esteem have been reported to be a risk factor for externalizing behavioral problems (Shin, Kang, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Allergische Rhinokonjunktivitis ist eine weitere allergische Erkrankung, die mit AD(H)S und mit depressiven Störungen assoziiert ist (20). Mögliche Ursachen für diese Verbindung bestehen darin, dass die störenden Symptome der allergischen Rhinokonjunktivitis und die dadurch verminderte Lebensqualität sowie damit verbundener Stress den Patienten kognitiv und emotional beeinträchtigen.…”
Section: Zusammenhang Von Allergischen Und Psychischen Erkrankungenunclassified